Antonio Ricaurte: the creation of a portray as a child-hero 1830- 1881 - Martínez Martín, Abel Fernando; Otálora Cascante, Andrés Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This paper describes Antonio Ricaurte’s life as a childhero and martyr in the Independence of Colombia (1792- 1814). So it begins with the academic, literary, poetic, iconographic and pedagogical background related to Jose Maria Espinosa’s paintings and drawings. After, it is consolidated in the Papel Periódico Ilustrado deBogotá journal, on the second half of the XIX century. Ricaurte’s polemic myth as a child hero is used during the conservative administrations (the regeneration andthe hegemony) and the Catholic Church in Colombia, to awake, in the children and young people, the love for the country during the commemoration of his anniversaries(Ricaurte’s birth and death). Hence, it helps in the process of nation construction by appealing to the children heroes. Same example is Los Niños Héroes de Chapultepec in the oficial Mexican history. This paper collects a mixture of written sources with the National Independence iconographic sources.